Peran Guru Dalam Pelaksanaan Projek Penguatan Profil Pelajar Pancasila Dan Profil Pelajar Rahmatan Lil Alamin di MAN 1 Bangka Barat - Septaviona, Septaviona; Febrino, Febrino; Dewi, Ratna (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research was motivated by indications that the Pancasila student dimensions had not been achieved, which should be the teacher’s responsibility to strengthen the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile in students. So, the research is needed to (1) Find out the role of teachers in implementing the Project for Strengthening the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile at MAN 1 Bangka Barat. (2) Knowing the role of teachers in strengthening the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile at MAN 1 Bangka Barat. This research uses a qualitative approach with a cas study type research. The subjects in this research were the school headmaster, deputy head of curriculum, teachers, and students. The data in this research was obtained through interviews, observation, and documentation. Based on the data, the research results can be concluded: 1) the role teachers in implementing the Project for Strengthening the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile at MAN 1 Bangka Barat has been carried out well, namely as project planner, facilitator, companion, supervisor and consultant, and moderator. 2) the ole teachers as a strengthener of the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile has not been implemented optimally, because teachers mostly direct from afar so that the failure to achieve the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile occurs due to a lack of reinforcement by the teacher and students innate character.